In vitro hair study, to evaluate the performance of 1% selenium sulfide +3% salicylic acid shampoo compared to 2% ketoconazole +2% salicylic acid shampoo in improving hair smoothness, hair softness, hair moisture, hair shine, hair manageability and reducing the hair frizz - Shivalkar, Aasmi V.; Surve, Meghana A.; Sahasrabudhe, Harshada A.; Malhotra, Deeksha; Sawant, Pravin N. (International Journal of Research in Dermatology, 2025)
Background: Recently, there’s been more focus on finding hair care products that improve quality, manageability, and scalp health. Different active ingredients are used in products to improve these properties, with selenium sulfide and salicylic acid being important for their antifungal and keratolytic effects. Therefore, this study evaluates the efficacy of a novel hair care formulation, 1% selenium sulfide and 3% salicylic acid shampoo (Product A), in improving hair quality compared to a benchmark product, 2% ketoconazole and 2% salicylic acid shampoo (Product B). The main goal was to evaluate the impact of these formulations on hair smoothness, softness, moisture, shine, manageability, and frizz reduction through an in-vitro hair swatch study. Methods: The study involved baseline treatment followed by the application of the respective shampoos, with subsequent evaluation of hair quality parameters by a trained expert panel. Results: Results indicated that both products significantly improved hair smoothness and softness. However, product A outperformed product B in hair manageability and frizz reduction, with a 20% improvement in manageability and a 32% reduction in frizz. Product B, while showing greater improvement in moisture retention (13% vs. 6%), experienced a decline in shine, whereas product A maintained shine levels. Conclusions: Statistical analysis revealed significant differences in performance, with product A showing superior results overall. These findings suggest that product A offers a more balanced and effective solution for hair care, particularly in manageability and frizz control. Further research, including clinical trials, is recommended to validate these results and explore long-term effects.